Modernisasi Pembelajaran Bahasa Arab di Dayah MUDI Mesra Samalanga Kabupaten Bireuen - Fauzan, Fauzan (Tarbawiyah Jurnal Ilmiah Pendidikan, 2017)
This article discusses the modernization of Arabic learning in Dayah MUDI Mesra, Samalanga Bireuen District. The attention and study of the teaching of Arabic is still important even in the pesantren. Because, but it is possible that the learning still needs improvement, considering that many pesantren are less concerned about the methods and the learning curriculum, whereas both are important aspects in the development of learning. This study is a research field of evaluation of education, by studying the teaching practice of the field of Arabic language study in Dayah MUDI Mesra Samalangan Bireuen District.